The Effects of Discounts and Bonus Packs on Impulse Buying for Consumers of Ramayana Flobamora Mall Kupang - Zacharias, Yelda; Lao, Hans (CV. Jala Berkat Abadi, 2024)
This research aims to determine the effect of discounts and bonus packs on unplanned purchasing behavior (impulse buying) among consumers of Ramayana Flobamora Mall Kupang. The type of research used in this research is a quantitative research method with an associative approach. The population in this research are consumers who have made purchases at Ramayana Flobamora Mall Kupang. The sampling technique was carried out using purposive sampling, obtaining a sample of 117 people. Data was collected using a questionnaire, then analyzed using multiple linear regression analysis with the help of Statistical Product and Service Solution (SPSS) 22.0 for Windows. Based on analysis tests on research results, the following results can be obtained: (1) discounts (X1) partially have a significant effect on impulse buying as evidenced by the t-count value of 7.409 > t-table 1.980 and the significance value of 0.000 < 0.05, (2) The bonus pack (X2) partially has no significant effect on impulse buying as evidenced by the t-count value of 1.302 < t-table 1.980 and the significance value of 0.195 > 0.05, (3) discount (X1) and bonus pack (X2) simultaneously (altogether) influence consumer impulse buying at Ramayana Flobamora Mall Kupang with an F-count value of 53.990 > F-table 3.08 and a significance value of 0.000 < 0.05.